2018
DOI: 10.3892/ol.2018.8428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allyl isothiocyanate on the viability and apoptosis of the human cervical cancer HeLa cell line in�vitro

Abstract: Abstract. The present study aimed to investigate the effect of allyl isothiocyanate (AITC) on the viability and apoptosis of the human cervical cancer HeLa cell line in vitro, and to explore the potential underlying mechanisms of this. HeLa cells were treated with varying concentrations of AITC for different durations. The cell viability was then measured using a Cell Counting kit-8 assay and the apoptosis rate of the cells was detected using flow cytometry. Additionally, the B cell lymphoma-2 (Bcl-2) and Bcl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
(26 reference statements)
1
25
0
Order By: Relevance
“…Moreover, ITCs have drawn attention owing to their capability to exert a broad spectrum of antitumor effects (9)(10)(11). Allyl isothiocyanate (AITC) is a constituent of naturally occurring ITCs and exerts multiple biological effects (such as anti-microbial, anti-inflammatory, anti-angiogenic and anticancer activities) (12)(13)(14)(15). AITC was found to inhibit cell proliferation and to facilitate apoptosis through Bcl-2/Bax imbalanced expression in human renal carcinoma GRC-1 cells (16).…”
Section: Sensitivity Of Allyl Isothiocyanate To Induce Apoptosis Viamentioning
confidence: 99%
“…Moreover, ITCs have drawn attention owing to their capability to exert a broad spectrum of antitumor effects (9)(10)(11). Allyl isothiocyanate (AITC) is a constituent of naturally occurring ITCs and exerts multiple biological effects (such as anti-microbial, anti-inflammatory, anti-angiogenic and anticancer activities) (12)(13)(14)(15). AITC was found to inhibit cell proliferation and to facilitate apoptosis through Bcl-2/Bax imbalanced expression in human renal carcinoma GRC-1 cells (16).…”
Section: Sensitivity Of Allyl Isothiocyanate To Induce Apoptosis Viamentioning
confidence: 99%
“…AITC is a volatile and water-insoluble compound derived from various cruciferous vegetables that exhibits multiple functions, such as anti-inflammation, neuroprotection, and anti-bacterial activity [38,39]. In addition, AITC is reported to have anti-cancer effects in various types of malignancies [40][41][42]. However, a study showed that AITC had no significant inhibitory effects on cell proliferation or stimulation of apoptosis in the human breast cancer cell line MDA-MB-231 [43].…”
Section: Allyl Isothiocyanatementioning
confidence: 99%
“…The early studies focused mainly on the ability of ITCs to inhibit the growth of cancer cells, recent studies showed that ITCs also suppress the survival and proliferation of existing cancer cells. Anticancer potency of ITCs on cancer cells via multiple mechanisms, including inhibition of carcinogen-activating enzymes, induction of carcinogen-detoxification enzymes, induction of apoptosis, and other mechanisms not yet well understood [4][5][6][7][8]. Apoptotic induction is of particular interest because it can be exploited for cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (SFA) obtained from broccoli is the most well-known example of a plant ITC with anticancer properties [5]. SFA was isolated from broccoli extracts as a potent inducer of mammalian cytoprotective enzymes [5][6][7]. Broccoli seeds and sprouts are rich sources of glucoraphanin (GRA), which is the chemical precursor of SFA [9].…”
Section: Introductionmentioning
confidence: 99%